Regulatory mechanisms of m6A RNA methylation in esophageal cancer: a comprehensive review - Long Wen; Long Wen; Jiang Fu; Zixu Wang; Rangping Xie; Rangping Xie; Shengjie Tang; Li Yu; Haining Zhou; Haining Zhou; Haining Zhou; Haining Zhou (Frontiers in Genetics)
Esophageal cancer is an aggressively malignant neoplasm characterized by a high mortality rate. Frequently diagnosed at an advanced stage, it presents challenges for optimal therapeutic intervention due to its non-specific symptoms, resulting in lost opportunities for effective treatment, such as surgery, radiotherapy, chemotherapy and target therapy. The N6-methyladenosine (m6A) modification represents the most critical post-transcriptional modification of eukaryotic messenger RNA (mRNA). The reversible m6A modification is mediated by three regulatory factors: m6A methyltransferases, demethylating enzymes, and m6A recognition proteins. These components identify and bind to specific RNA methylation sites, thereby modulating essential biological functions such as RNA processing, nuclear export, stability, translation and degradation, which significantly influence tumorigenesis, invasion, and metastasis. Given the importance of m6A modification, this paper offers a comprehensive examination of the regulatory mechanisms, biological functions, and future therapeutic implications of m6A RNA methylation in the context of esophageal cancer.